Physico-Morphological Attributes, Freezability, Fertility and their Correlations in Jaffarabadi Buffalo Bull Semen - Vijyeta, Hardipsinh P; Kavani, Fulabhai S; Vagh, Arshi A; Vala, Karsan B; Savsani, Harish H; Kapadiya, Pratik S; Raval, Rupesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out on semen of six Jaffarabadi buffalo bulls, aged 6-8 years, under twice weekly semen collection schedule. In all 36 semen ejaculates (6/bull) were evaluated for routine physical characteristics including sperm quality and oxidative stress parameters at pre-freeze and post-thaw stages of cryopreservation and fertility using different Sericin concentrations in AndroMed® extender. All bulls donated milky-white semen with identical mean mass motility score, while ejaculate volume and sperm concentration differed significantly among bulls. The values of sperm progressive motility (%), viability (%), abnormality (%), HOST reactivity (%), acrosome integrity (%), lipid peroxidation (MDA µM) and total antioxidant capacity (TAC µM) of pre-freeze (on dilution) and post-thawed semen averaged 84.24 ±0.24 & 53.42±0.32, 82.43±0.26 & 57.38±0.49, 6.14±0.12 & 13.56±0.22, 72.84±0.31 & 45.65±0.48, 81.56±0.35 & 49.73 ±0.52, 7.71±0.04 & 8.35±0.05, and 315.80±5.99 & 292.89±7.40, respectively. The overall first service conception rate achieved was 36.73 (551/1500) %, and it varied from 28.00 to 44.66% between levels of Sericin. Pearson’s correlations amongst the pre-freeze as well as post-thawed semen parameters, and of pre-freeze with post-thawed semen parameters including CRs of frozen-thawed semen worked out using bull-wise and additive-wise 30 mean values revealed significant positive associations among sperm motility, viability, acrosome integrity, HOST reactive sperm, total antioxidant capacity (TAC), and first service CR, and all these had negative correlations with abnormal sperm and the lipid peroxidation (MDA) status in both pre-freeze and post-thawed semen. Further, the post-thawed sperm quality and fertility could be predicted well with highly significant positive correlations of pre-freeze sperm quality parameters and TAC in Jaffarabadi buffalo bulls.